Pemberian Bantuan Bencana Alam Tanah Lonsor Kampung Mbenti Distrik Minyambouw - Zulkarnain; Lilis Indrayani; Yammes J Batkunde; Sabinus Rainer N. Chiristi; Engelbert Worabai; Samuel Mathias Dauth Menai; Melvi Marhaba; Melva Marhaba (CV. Multi Kreasi Media, 2024)
This Community service activities